Social learning, search and heterogeneity of payoffs - Edward Cartwright (University of Kent, Department of Economics, 2007)
We consider a simple model that combines elements of search and social learning. Acting in sequence, and observing the action adopted by a previous agent, agents must search for an action. We explore why agent heterogeneity may increase expected payoffs and demonstrate that social learning may be most effective if agents are heterogenous.
Keywords: C7; D8; 330; Social learning; search; herding; Social Capital; Lernprozess; Spieltheorie